2018
DOI: 10.1186/s13756-018-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface area wiped, product type, and target strain impact bactericidal efficacy of ready-to-use disinfectant Towelettes

Abstract: BackgroundDisinfectant products are often used on environmental surfaces (e.g. countertops, patient beds) and patient care equipment in healthcare facilities to help prevent the transmission of healthcare-associated infections. Ready-to-use (RTU) disinfectants in the form of pre-wetted towelettes are increasingly popular among healthcare facilities. Currently, the EPA does not require disinfectant manufacturers to include a recommended maximum surface area per towelette on their product labels. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
6
28
0
Order By: Relevance
“…Quaternary ammonium towelettes transfer more P. aeruginosa than hydrogen peroxide towelettes Hydrogen peroxide products transferred signi cantly less log 10 CFU/100 cm 2 to previously uncontaminated surfaces than QA products. This is similar to previous ndings by our group where we demonstrated that hydrogen peroxide disinfectant towelettes were more bactericidal against S. aureus and P. aeruginosa inoculated on 97 mm Formica disc than quaternary alcohol towelettes [18]. This signi cant difference could be explained by the potential for accelerated HP products to produce hydroxyl free radicals which are generally more bactericidal than quaternary alcohols [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Quaternary ammonium towelettes transfer more P. aeruginosa than hydrogen peroxide towelettes Hydrogen peroxide products transferred signi cantly less log 10 CFU/100 cm 2 to previously uncontaminated surfaces than QA products. This is similar to previous ndings by our group where we demonstrated that hydrogen peroxide disinfectant towelettes were more bactericidal against S. aureus and P. aeruginosa inoculated on 97 mm Formica disc than quaternary alcohol towelettes [18]. This signi cant difference could be explained by the potential for accelerated HP products to produce hydroxyl free radicals which are generally more bactericidal than quaternary alcohols [20].…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of strain, the cross-contamination risk presented by disinfectant towelettes was highly product-dependent as HP3, QA1 and QA3 wipes had signi cantly lower log 10 CFU/100 cm 2 postdisinfection than HP1 and QA2. The observed differences may be explained by factors as differences in the wipe material type [33], active ingredient class [17], and differences in the amount of liquid released onto the test surfaces [18] during the wiping process. The disinfectant towelette substrate type has been demonstrated to play a major role in the physical removal of pathogens from test surfaces [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was evident as the 0.5 m 2 and 1 m 2 surfaces were visibly wet after the wiping process. In a previous study by our group [22], we found that the percent of liquid released per 0.1 m 2 of a Formica surface significantly decreased as the surface area wiped increased. However, overall, there were no significant differences in the log 10 CFU/100 cm 2 of spores transferred to the 0.5 m 2 1.0 m 2 , 1.5 m 2 and 2.0 m 2 surface areas.…”
Section: Disinfectant Wipes Cross-contaminate Hard Non-porous Surfacesmentioning
confidence: 63%
“…In addition, the Environmental Protection Agency (EPA) has no recommendation on the maximum surface area that could be disinfected with a towelette in order to optimize bactericidal efficacy, while minimizing the risk of cross-contaminating low risk surfaces. In prior work by our group, we found that the efficacy from pre-wetted disinfectant wipes was related to the ability to keep surfaces wet for the label contact time, so "stretching" a wipe to wipe larger areas than the wipe can disinfectant may create risks of suboptimal disinfection and cross-contamination [22].…”
mentioning
confidence: 98%